Participatory foresight for technology assessment - Mahshid Sotoudeh; Niklas Gudowsky (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2018)
Technology assessment (TA) frequently uses forward-looking methods  to anticipate socio-technical changes and their corresponding implications  to deduce advice for policy and society. In recent years, participatory  methods have increasingly been applied to identify the expectations of society towards future technologies. In this context, several  TA projects have developed, applied and adapted a participatory  foresight method to engage citizens as well as other actor groups into  co-generating advice for research and innovation agenda setting in a standardized process; namely, the multi-perspective and multi-step  CIVISTI method (Citizens’ Visions on Science, Technology and Innovation). Over the course of the past ten years, about 560 lay citizens without  specialised knowledge on technology and innovation and 610 experts  and stakeholders have taken part in these processes of co-generation  of knowledge. In this contribution, we use our experience with  this method and elaborate some criteria for the evaluation of knowledge  co-generation and mutual learning in participatory foresight processes  within TA.